Addressing an urgent climate-related concern: Migration and displacement. CGIAR Issue Brief Series for Informing COP 29 | Number 9 - Ramos, C.; Takaindisa, J.; Craparo, A.; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR Climate Change Impact Platform, 2024)
Climate change is contributing to unprecedented levels of displacement, putting millions of vulnerable populations at risk of deteriorating livelihoods. Displaced persons are often excluded in climate policies and interventions that directly impact them, highlighting the need to actively integrate them into decision-making processes. Migration can be an important adaptation strategy that benefits migrants and host communities, supporting individuals and communities to build resilience while reducing their exposure to climate risk.